Biopsy or Biomarker? Children With Minimal Change Disease Have a Distinct Profile of Urinary Epidermal Growth Factor - Lodeweyckx, Niels; Wouters, Kristien; Ledeganck, Kristien J.; Trouet, Dominique (Frontiers in Pediatrics, 2021)
ABSTRACT Background In this study , the profile of urinary EGF excretion (uEGF/u creat ) was mapped in children presenting with prolonged proteinuria or with nephrotic syndrome refractory to or dependent of steroids . We investigated whether uEGF/u creat could be linked to the underlying biopsy result, taking into account its response to immunosuppressive medication and to ACE-inhibition, as well as genetic predisposition. Methods Ninety eight pediatric patients with initial presentation of nephrotic syndrome or prolonged proteinuria were included in this study, along with 49 healthy controls and 20 pediatric Alport patients. All patients had a normal kidney function and were normotensive during the course of the study, either or not under ACE-inhibition. In repeated urine samples, uEGF was measured and concentration was normalized by urine creatinine. In order to compare diagnosis on kidney biopsy, genetic predisposition and response of uEGF/Ucreat to immunosuppression and to ACE-inhibition, uEGF/uCreat is studied in a linear mixed effects model . Results Patients with Minimal Change Disease (MCD) showed a significantly different profile of uEGF/U creat in comparison to healthy children, as well as compared to patients with Focal Segmental Glomerulosclerosis (FSGS) or another glomerulopathy on kidney biopsy. The response of uEGF/Ucreat to ACE-inhibition was absent in minimal change disease and contrasted with an impressive beneficial effect of ACE-inhibition on uEGF/u creat in FSGS and other proteinuric glomerulopathies. Absence of a genetic predisposition was also associated with a significantly lower uEGF/U creat. Conclusions Despite preserved kidney function, children with a proteinuric or nephrotic glomerular disease on kidney biopsy show a significantly lower uEGF/Ucreat, indicative of early tubulo-interstitial damage, which appears reversible under ACE-inhibition in any underlying glomerulopathy except in minimal change disease. In view of the distinct profile of uEGF/ucreat in minimal change disease compared to other glomerulopathies, and the link between genetic predisposition and uEGF/u creat, our study suggests that uEGF/Ucreat might be able to distinguish minimal change disease from other proteinuric glomerular diseases.